6(x-11)=15-4x(-2+3)+5x

Simple and best practice solution for 6(x-11)=15-4x(-2+3)+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-11)=15-4x(-2+3)+5x equation:



6(x-11)=15-4x(-2+3)+5x
We move all terms to the left:
6(x-11)-(15-4x(-2+3)+5x)=0
We add all the numbers together, and all the variables
6(x-11)-(15-4x1+5x)=0
We multiply parentheses
6x-(15-4x1+5x)-66=0
We get rid of parentheses
6x+4x1-5x-15-66=0
We add all the numbers together, and all the variables
5x-81=0
We move all terms containing x to the left, all other terms to the right
5x=81
x=81/5
x=16+1/5

See similar equations:

| 4+124x=320 | | −7.6+3.8=x | | -12(x-1)=(x+13) | | 15.75x+8.50=15.75x+7.50 | | 3x-47=-5 | | 5n=7=2 | | 19=11g-14 | | 4+124x=124 | | (5x-9)+(4x+7)=180 | | 18÷y=4= | | v-3-v+47=180 | | 21+15v= | | k–7=–12 | | 4.5x+45=12x | | 0=(-2)+5x | | 2b−3=87 | | 5(3m-5)+9m=-1 | | 3x-0.5=3.5= | | -77p-80-3+5p=-77 | | 20x-100=-100 | | -7(x-3)=6(3x+5) | | 5y–1.2=48.8= | | (3a+5)(2a+4)=30a²+60a | | 7x+4+x-22=180 | | -4(1.75+x=18 | | 0=-2+(x/5) | | 0.4n+3=11= | | 26/3x=6 | | x/7+15=8 | | -32n=8n | | b+4+46+2b+10=180 | | 7x+3=2x+187x+3=2x+18 |

Equations solver categories